Overlooking the Border : Narratives of a Divided Jerusalem - Hercbergs, Dana (Book collections on Project MUSE., 2018)
"Overlooking the Border: Narratives of Divided Jerusalem by Dana Hercbergs continues the dialogue surrounding the social history of Jerusalem. The book's starting point is the border that separated the city between Jordan and Israel in 1948-1967, a lesser-known but significant period for cultural representations of Jerusalem. Based on ethnographic fieldwork, the book juxtaposes Israeli and Palestinian personal narratives about the past with contemporary museum exhibits, street plaques, tourism, and real estate projects that are reshaping the city since the decline of the peace process and the second intifada. What emerges is a portrayal of Jerusalem both as a local place with unique rhythms and topography and as a setting for national imaginaries and agendas with their attendant political and social tensions." -- Back cover.